An investigation from the standpoint of consumer behavior on the effects of the choice of media on the performance of marketing campaigns (International Journal of Food and Nutritional Sciences, 2022)
Over a century has passed since the invention of advertising. Technology advancements have produced a variety of media for advertising. As a result, there are more possibilities for advertisers to select the ideal advertising media. Choosing the best medium for marketing is one issue this poses for advertisers. An empirical study from the viewpoint of consumer behavior was done to ascertain the effect of media choice on the efficacy of marketing. This descriptive study uses a single cross-sectional design and quantitative methods. With 155 participants, this study was done in Chandigarh. SPSS and PLS were used to analyze the data. This study's findings indicate that media selection positively and significantly affects the efficacy of advertising. It demonstrates the significance of media choice.